Susceptibility to SARS-CoV-2 infection in patients undergoing chemotherapy and radiation therapy - Claudia Rita Corso; Natalia Mulinari Turin de Oliveira; Daniele Maria-Ferreira (Elsevier, 2021)
The outbreak of the new coronavirus disease (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has rapidly become a public health emergency of international concern, especially affecting the elderly people and patients with chronic disease, such as hypertension and respiratory syndromes. Patients undergoing chemotherapy treatment (e.g., bleomycin, cyclophosphamide, methotrexate, monoclonal antibodies, and paclitaxel therapy) are vulnerable to the development of respiratory syndromes induced by chemotherapeutic agents and are also more susceptible to viral infections as they are immunosuppressed. Neutropenia is an important risk factor for increased vulnerability to infections, as a respiratory syndrome involves an array of immune cells maintaining the balance between pathogen clearance and immunopathology. However, the differential diagnosis of pulmonary symptoms in cancer patients is broad, with complications being related to the malignancy itself, treatment toxicity, and infections. The risk factors depend on the specific type of cancer, chemotherapy, patient characteristics, and comorbidities. Thus, this review discusses the main events implicated in immunosuppression caused by chemotherapy and radiation therapy and the association of immunosuppression and other factors with SARS-CoV-2 infection susceptibility in cancer patients; and, importantly, how to deal with this situation in face of the current pandemic scenario.